IMPLEMENTATION OF THE WATERFALL METHOD IN THE DESIGN OF A WEBSITE-BASED BOOK LENDING SYSTEM - Teguh Cahyono; Susi Setianingsih; Dadang Iskandar (Jurnal Teknik Informatika (Jutif), 2022)
The application of information technology in the library can increase the acceleration of information to the public. One of the library activities that quite a lot of using paper media is borrowing books. The use of ledgers in borrowing books is tantamount to spending a lot of paper with large data and will cause piles later. Therefore, it is necessary to update the book lending system with integrated information technology in order to increase efficiency and effectiveness in the library. The Book Borrowing System or known as TEMANKU is a book lending system that is integrated with the internet to improve operations in book lending activities in the library. In carrying out this activity, a method must be used to implement it. The waterfall method was chosen because it is easy to implement and the system implementation can be implemented in a better and structured manner. On the other hand, the approach used in the design uses data flow diagram ( DFD). The results of this study resulted in the design of a website-based book lending system.